A Critical Review of the Climate-Related Reporting Requirements in the Financial Service Sector - Spasić, Dejan; Denčić-Mihajlov, Ksenija; Poposki, Klime (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
The signing of the Paris Agreement and the adoption of the UN 2030 Agenda for Sustainable Development proved a radical change in global attitudes towards the climate change and sustainable development. Sustainability and the transition to a low-carbon and more resource-efficient are the key endeavours in ensuring long-term competitiveness of the EU economy. The paper deals with the challenges the EU faces with while reallocating capital flows for sustainable investments and offers a critical overview of the new EU guidance for companies on climate-related reporting and the adoption of the EU taxonomy. Given that risk identifying, modeling and managing are at the core of the insurance industry, and that the risk related to climate changes are today the most significant long-term risk, a special attention is given to the disclosure of climate-related information from the perspective of the insurance sector.